Hepatitis B Virus Reactivation Associated With Therapeutic Interventions - Chang, Young; Jeong, Soung Won; Jang, Jae Young (Frontiers in Medicine, 2022)
Hepatitis B virus (HBV) reactivation associated with various therapeutic interventions is an important cause of morbidity and mortality in patients with current or resolved HBV infection. Because no curative treatment for HBV infection is yet available, there are many individuals at risk for HBV reactivation in the general population. Populations at risk for HBV reactivation include patients who are currently infected with HBV or who have been exposed to HBV in the past. HBV reactivation and its potential consequences is a concern when these populations are exposed to anti-cancer chemotherapy, immunosuppressive or immunomodulatory therapies for the management of various malignancies, rheumatologic diseases, inflammatory bowel disease, or solid-organ or hematologic stem cell transplantation. Accordingly, it has become important to understand the basics of HBV reactivation and the mechanisms by which certain therapies are more susceptible to HBV reactivation. This review aims to raise the awareness of HBV reactivation and to understand the mechanisms and the risks of HBV reactivation in various clinical settings.